Dinamika Konflik Politik di Desa: Proses dan Dampaknya terhadap Tata Kelola Pemerintahan - Kasmawanto, Zuli (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2025)
Villages in the post-decentralization era have evolved into dynamic arenas of local politics alongside the expansion of village governance authority. This study aims to analyze the dynamics of political conflict in villages and its impact on village governance. The research employs a qualitative approach with a case study design conducted in Kuluran Village, Kalitengah Subdistrict, Lamongan Regency. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed interactively. The findings indicate that political conflict in villages is rooted in post–village head election contestation of interests, reinforced by patronage relations, unmet political expectations, and weak reconciliation mechanisms. The conflict develops from differences in policy perspectives into escalating tensions among village political actors, resulting in delays in policy decision-making, declining quality of public services, and weakened community participation. This study underscores the importance of managing village political conflict through institutional and participatory mechanisms to support democratic village governance.